Measurement of tibiofemoral angle in Nepalese children: a clinical study in normal subjects between ages of 1-8 years - Prajapati, Akesh (Journal of Chitwan Medical College, 2018)
In evaluation of genu valgum/varum Tibiofemoral angle (TF), Inter-condylar Distance (IC) and Inter-malleolar Distance (IM) are commonly measured. In this study normal limits and mean values of TF angle IC/IM distances was determined in 413 normal Nepalese children aged between 1-8 years using clinical methods. A significantly higher degree of valgus angle was noted compared to other studies performed in different races. The maximal mean valgus angle was 10.5 at 4-5 years for boys and 10.6 at 6-7 years for girls. Conclusion: A measurable varus or valgus angle higher than 11 degrees during this period should be considered abnormal.